2022
DOI: 10.3389/fpubh.2022.935243
|View full text |Cite
|
Sign up to set email alerts
|

The way forward to achieve high COVID-19 vaccination and revaccination coverage in a city amid a period of tranquility

Abstract: BackgroundAmid the current COVID-19 pandemic, there is an urgent need for both vaccination and revaccination (“boosting”). This study aims to identify factors associated with the intention to receive a booster dose of the coronavirus (COVID-19) vaccine among individuals vaccinated with two doses and characterize their profiles in Hong Kong, a city with a low COVID-19 incidence in the initial epidemic waves. Among the unvaccinated, vaccination intention is also explored and their profiles are investigated.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 42 publications
6
10
1
1
Order By: Relevance
“…Taking a person-centered approach, we empirically identified four different profiles of HCWs based on their scores in 5Cs measure [ 14 ]. The majority of our population of HCWs falls into the believer profile, converging with results from previous research, defined by the highest levels of confidence and collective responsibility, and lowest levels in complacency and constraints [ 23 , 25 , 27 ]. Furthermore, in line with Zhang and colleagues [ 25 ], in our study, calculation was slightly below average levels, and it was the profile with the lowest levels of calculation.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Taking a person-centered approach, we empirically identified four different profiles of HCWs based on their scores in 5Cs measure [ 14 ]. The majority of our population of HCWs falls into the believer profile, converging with results from previous research, defined by the highest levels of confidence and collective responsibility, and lowest levels in complacency and constraints [ 23 , 25 , 27 ]. Furthermore, in line with Zhang and colleagues [ 25 ], in our study, calculation was slightly below average levels, and it was the profile with the lowest levels of calculation.…”
Section: Discussionsupporting
confidence: 86%
“…In another similar study performed using the same 5C framework in the same working population (nurses), Leung and colleagues identified five latent profiles of hesitant: believers (high confidence, collective responsibility; low complacency, constraint), skeptics (opposite to the believers), outsiders (low calculation, collective responsibility), contradictors (high in all 5C constructs), and middlers (average levels in all 5C factors) [ 23 ]. In line with these results, Kwok and colleagues identified four latent profiles: believers (high confidence, high collective responsibility, low complacency, and low constraint), fence-sitters (average scores in all 5C factors), apathetics (low in calculation, high in complacency, and high constraint), and skeptics (low confidence, low collective responsibility, high complacency, and high constraint) [ 27 ].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Apart from factors such as worries about COVID-19 infection and vaccination, physical fitness, social deprivation, and sense of belonging at school and the community ( 10 , 11 ), their attitude toward the government was also found as a key factor to the compliance with vaccination and other COVID-19 containment measures imposed by the government in the literature ( 12 ). In general, the higher the level of trust, the greater the willingness and intention of vaccination would be ( 13 17 ). Nonetheless, previous cross-country research showed that younger people tend to have lower trust in their governments ( 18 ).…”
Section: Introductionmentioning
confidence: 99%